Human genetic variation: New challenges and opportunities for doping control - Schneider, A. J.; Fedoruk, M. N.; Rupert, J. L. (Journal of Sports Sciences, 2012)
Sport celebrates differences in competitors that lead to the often razor-thin margins between victory and defeat. The source of this variation is the interaction between the environment in which the athletes develop and compete and their genetic make-up. However, a darker side of sports may also be genetically influenced: some anti-doping tests are affected by the athlete's genotype. Genetic variation is an issue that anti-doping authorities must address as more is learned about the interaction between genotype and the responses to prohibited practices. To differentiate between naturally occurring deviations in indirect blood and urine markers from those potentially caused by doping, the "biological-passport" program uses intra-individual variability rather than population values to establish an athlete's expected physiological range. The next step in "personalized" doping control may be the inclusion of genetic data, both for the purposes of documenting an athlete's responses to doping agents and doping-control assays as well facilitating athlete and sample identification. Such applications could benefit "clean" athletes but will come at the expense of risks to privacy. This article reviews the instances where genetics has intersected with doping control, and briefly discusses the potential role, and ethical implications, of genotyping in the struggle to eliminate illicit ergogenic practices.